Aortic Stenosis Review: Pathophysiology, Clinical Symptoms, and Key Diagnostic Signs - Maharani, Baiq Syarifaturrayyan; Febriana, Nanggi Qoriatul; Sari, Padmi Kartika; Maudina, Baiq Zaskia; Hakim, Baiq Sheila Oktalia (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Aortic stenosis is among the most common valvular heart diseases, particularly in the elderly, and remains a major cause of morbidity and mortality. It is characterized by narrowing of the aortic valve, leading to increased afterload, compensatory left ventricular hypertrophy, and eventual heart failure or sudden death. To summarize updated evidence on the pathophysiology, clinical manifestations, and diagnostic signs of aortic stenosis. A literature review was conducted through systematic searches of PubMed, ScienceDirect, and Google Scholar, prioritizing publications from the last ten years. Articles on anatomy, physiology, pathophysiology, clinical features, diagnostic findings, and disease progression were critically analyzed. Aortic stenosis develops through degenerative calcification, rheumatic autoimmune inflammation, or congenital malformation. Disease progression leads to elevated transvalvular gradient, reduced stroke volume, and left ventricular hypertrophy. Typical symptoms include angina, syncope, and heart failure. Key diagnostic signs are a crescendo–decrescendo systolic ejection murmur radiating to the carotid arteries and the Gallavardin phenomenon. Aortic stenosis is a progressive valvular disease with complex pathophysiological mechanisms. Comprehensive understanding of its biological processes, clinical manifestations, and diagnostic signs is essential to support early detection and timely management. Such efforts may reduce morbidity and mortality while paving the way for innovative therapeutic strategies in the future.